RETRACTED: The Effect of Physical Work Environment, Work Motivation and Compensation on The Performance of Employees of The Directorate General of Human Rights - Desi Safitri; Ahmad Cik; Kumba Digdowiseiso (Journal of Social Science)
This study aims to analyze the influence of the physical work environment, work motivation and compensation on the performance of employees of the Directorate General of Human Rights. This type of research uses quantitative techniques, descriptive methods and data analysis methods using iferential analysis of multiple linear regression and uses primary data in the form of a closed questionnaire to 100 respondents assisted by using the Stastical Product and Service Solution (SPSS) program application version 23.0. The results of the analysis in this study prove that the three variables of physical work environment, work motivation and compensation have a significant influence on the defendent variables, namely performance in employees. From the results of this study, it is expected that the Institute will pay attention to and evaluate employee performance in order to improve employee performance in order to be good and effective.